The Effect of Service Quality on Patient Satisfaction in Obstetrics and Gynecology Polyclinic of PKU Muhammadiyah Gombong Hospital, Kebumen District During the Covid-19 Pandemic - Wulan Rahmadhani; K Kusumastuti; Phan Trieu Phu MD (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Health is one of the indicators of community welfare, so the community needs quality health services to meet their basic needs. To improve services and increase patient satisfaction, hospitals need to apply the Covid-19 policy in screening and service flows which are predicted to affect patient satisfaction. The aim of this study was to determine the effect of service quality on patient satisfaction during the COVID-19 pandemic. The research method in this study used a cross-sectional approach. The population was outpatients at the obstetrics and gynaecology polyclinic. The sample was determined using the accidental sampling technique with a total of 360 patients. The data were analyzed to determine the most dominant factor by using a logistic regression test. Based on the results of multivariate analysis, the variables with the greatest influence on patient satisfaction are the assurance variable (95% CI 1.50-6.06 with a p-value of 0.012), empathy (95% CI 1.38-4.65 with a p-value of 0.006), and tangible (95% CI 1.04- 4.08 with a p-value of 0.001). Based on the results, it can be concluded that there is a relationship between the dimensions of service quality and patient satisfaction. The quality of service during the Covid-19 pandemic is considered good but needs to be optimized on the dimensions of assurance, empathy, and tangible.  Abstrak: Kesehatan adalah indikator kesejahteraan masyarakat yangpaling utama, dan untuk memenuhi kebutuhan dasarnya masyarakat membutuhkan pelayanan yang bermutu. Rumah sakit berusaha meningkatkan pelayanan dan kepuasan pasien perlu adanya kebijakan mengatasi penularan Covid-19 berupa prosedur pelayanan, keharusan screening, serta alur proses pelayanan yang berubah diduga juga berpengaruh terhadap kepuasan pasien dan mutu pelayanan.  Tujuan penelitian ini bertujuan untuk mengetahui pengaruh mutu pelayanan terhadap kepuasan pasien dalam masa pandemic covid-19. Metode Penelitian menggunakan pendekatan cross sectional. Populasi penelitian adalah pasien rawat jalan di poliklinik kebidanan dan kandungan, Prosedur sampel Accidental Sampling sebanyak n=360. data hasil survey di analysis untuk mengetahui factor yang paling dominan dengan menggunakan uji regresi logistic.  Berdasarkan hasil analisis multivariate variabel yang paling besar pengaruhnya terhadap kepuasan pasien adalah variabel Assurance dengan nilai 95%CI 1.50-6.06 dan p =0.012, Emphaty 95%CI 1.38-4.65 p=value 0.006 dan Tangiable dengan nilai 95%CI 1.04-4.08 dan p=value 0.001. Berdasarkan hasil pada penelitian ini dikatakan bahwa terdapat hubungan pada dimensi mutu pelayanan dengan kepuasan pasien. Mutu pelayanan yang terjadi selama masa pandemi Covid-19 dinilai mulai sudah baik, akan tetapi harus di tingkatkan da dioptimalkan pada dimensi jaminan, emphaty dan tangibles.